Pegaruh Keteladanan Guru Terhadap Perilaku Keagamaan Siswa - Ade Abdul Muqit; Abu Maskur (Fakultas Tarbiyah Institut Ilmu Al-Qur'an (IIQ) Jakarta, Indonesia, 2022)
The research aims to find out to what extent of the influence of teacher exemplary on religious behavior at SD Al-Bayan Islamic School Tangerang. This research is a quantitative research with data collection techniques using questionnaires, where students as respondents in this study. The population in this study were 300 students, of which 100 students were used as samples in this study. The results of this study indicate that there is a positive relationship between teacher exemplary (X) and students' religious behavior (Y) with the formula = 46,705 + 0.798 X. Furthermore, because the correlation coefficient r = 0.452, it can be obtained that the coefficient of determination is R2 = 0.205 which means that 20.5% of the variance of student religious behavior can be explained by the example of teachers at SD Al-Bayan Islamic School, through the regression equation = 46,705 + 0.798 X. In other words, the contribution of exemplary teachers to the religious behavior of students at SD Al-Bayan Islamic School School Tangerang amounted to 20.5% while the remaining 79.5% was due to other factors.